The Political Economy of Coalition in Indonesia - Sanjaya, Muhammad Ryan (Universitas Airlangga, 2016)
Politics as an art of bargaining has gain prominent momentum following the victory of the president-elect Joko Widodo in Indonesia in 2014. This paper estimates the value of political parties under uncertainties over two possible coalitions: the Great Indonesia Coalition (Koalisi Indonesia Hebat, KIH) that supports Joko Widodo, and the Red & White Coalition (Koalisi Merah Putih, KMP) that supports Prabowo Subianto, the president candidate from the Gerindra Party. The estimation shows that the Golkar, the second largest earner of seats in the parliament, is more valuable for KMP, making them expensive to be maintained within this coalition. It suggests that the best choice for Golkar is to jump to KIH, unless the KMP provides substantial payoff to lure this party. Nonetheless, the pure strategy Nash equilibrium in a non-cooperative game of political bargaining shows that even though a party has small fair values, but it still has decisive impact in the bargaining table of a coalition.